Teaching Phonemic Awareness to Filipino Students: Bridging Culture and Pedagogy: A Case Study - Garganera, Japhet Mari (Program Studi Pendidikan Bahasa Inggris, 2025)
This case study explored the issues and challenges in teaching phonemic awareness to Filipino students, specifically on how culture, pedagogy, and instructions work hand in hand. Furthermore, it seeks to explore how educators navigate these challenges, considering linguistic diversity, teaching methodologies, and resource availability. This study implemented a Descriptive-Correlational-Explanatory research design, which was used to determine the cultural and pedagogical issues in teaching phonemic awareness to Filipino students, and analyze their causal relationship. The data used in this study is derived from interviews with randomly selected students and from related literature studies in the same field. Based on the analysis of the data, it was found that teaching phonemic awareness to Filipino students presents unique challenges due to linguistic diversity of the country creating language interference that causes pronunciation difficulties, and assessment anxiety, coupled with lack of resources and training of teachers that further extrapolates the need for a multifaceted educational reform.